Membrane Concentrate Management Model of Biologically Pre-treated Textile Wastewater for Zero-Liquid Discharge - Altinay, Aysegul Derya; Yazagan, Alper; Koseoglu-Imer, D. Y.; Keskinler, Bülent; Koyuncu, Ismail (Springer Int Publ Ag, 2022)
Membrane technology is an outstanding alternative for treating complex textile wastewaters. However, difficulties in the management of the resultant concentrate are the main disadvantage of these membrane technologies. This study is focused on the development of integrative management for membrane concentrate of textile effluent under the principle of discharge regulations that aim to achieve zero-liquid discharge (ZLD). Thus, biologically treated textile wastewater (BTTW) is fed to nanofiltration (NF) and reverse osmosis (RO) membranes with ultrafiltration (UF) pre-treatment, separately. NF concentrates (NFC) and RO concentrates (ROC) are further treated with electrocoagulation (EC) and electro-Fenton (EF) to remove COD and color. After the EC and EF steps, the electrodialysis (ED) method is used for ion removal. Operational costs of each process are calculated. Through the NF of BTTW > 65% COD and 92% color removals were achieved, whereas with the RO process, > 65% COD and 98% color removals were obtained. For NFC, > 80% COD and 91% color removal efficiencies were achieved with EC + ED processes and 57% COD and almost total color removal was achieved with EF + ED processes. For ROC, 71% COD and 85% color removals were obtained with EC + ED processes and 85% COD and 98% color removal was observed with EF + ED processes. Additionally, efficient treatment and concentrate management options were investigated for textile effluent.
Keywords: Membrane concentrate; Electrocoagulation (EC); Electro-Fenton (EF); Electrodialysis (ED); Techno-economic analysis; Zero-liquid discharge